1976
DOI: 10.1017/s0025315400021020
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low metal levels on a clonal hydroid

Abstract: A sensitive and precise bioassay has been developed, using the colonial hydroid Campanularia flexuosa, for measuring the sublethal effects of marine contaminants in terms of the inhibition of colonial growth rate. A single clone can be cultured simply in the laboratory for indefinite periods. Thresholds of sensitivity to three metals in 11-day experiments were Hg 2 + 1-6-1-7/tg/1, Cu 2+ 10-13/ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

1976
1976
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 75 publications
1
39
1
Order By: Relevance
“…These are, for example, larvae of oysters and crustaceans or fish embryos, which are considerably more sensitive to heavy metals than are the reproductive adult stages. Marine hydroid polyps also respond sensitively to heavy metals (Karbe, 1972;Stebbing, 1976;Fischer, 1978): e. g. Laomedea loveni responds even to cadmium concentrations in the low #g 1-1 range (Scholz et al, 1978;Theede et al, 1979b). However, experimental determination of tolerance limits must take abiotic environmental factors into account, because they may be of importance for in-situ survival, especially in estuaries and coastal areas (Eisler, 1971;Olson & Harrel, 1973;von Westernhagen et al, 1974;Jones, 1975;Rosenberg & Costlow, 1976;Sullivan, 1977;Voyer et al, 1977;Weis & Weis, 1978;Lehnberg & Theede, 1979;Theede et al, 1979b).…”
Section: Effects Of Environmental Factors On Toxicitymentioning
confidence: 99%
“…These are, for example, larvae of oysters and crustaceans or fish embryos, which are considerably more sensitive to heavy metals than are the reproductive adult stages. Marine hydroid polyps also respond sensitively to heavy metals (Karbe, 1972;Stebbing, 1976;Fischer, 1978): e. g. Laomedea loveni responds even to cadmium concentrations in the low #g 1-1 range (Scholz et al, 1978;Theede et al, 1979b). However, experimental determination of tolerance limits must take abiotic environmental factors into account, because they may be of importance for in-situ survival, especially in estuaries and coastal areas (Eisler, 1971;Olson & Harrel, 1973;von Westernhagen et al, 1974;Jones, 1975;Rosenberg & Costlow, 1976;Sullivan, 1977;Voyer et al, 1977;Weis & Weis, 1978;Lehnberg & Theede, 1979;Theede et al, 1979b).…”
Section: Effects Of Environmental Factors On Toxicitymentioning
confidence: 99%
“…In earlier work with the colonial hydroid Campanularia (Laomedea) flexuosa, we considered the growth of colonies exposed to various toxic inhibitors (Stebbing, 1976). Initially, mean growth rates over entire experiments (1 1 d) were used to determine concentration-response curves and threshold concentrations were derived from them.…”
Section: Introductionmentioning
confidence: 99%
“…This work is a development of a bioassay technique, using a clonal hydroid {Campanu-laria flexuosa), which was intended primarily to study contaminants of sea water at levels comparable to those found in polluted estuaries (Stebbing, 1976). Sensitivity to low metal levels was achieved using the mean colonial growth rate over 11-day periods as an index of response.…”
Section: Introductionmentioning
confidence: 99%
“…Karbe (1972) has shown that this process also occurs when a stress is induced experimentally with toxic concentrations of metal ions. Degeneration is inevitably preceded by a slowing in colonial growth rate, which is the index of response we have been using in our allied study on metal toxicity (Stebbing, 1976). Degenerative processes in other organisms often involve autolysis by lysosomal hydrolases (Miller & Wolfe, 1968).…”
Section: Introductionmentioning
confidence: 99%